AKIBAT PEMILIHAN FORUM DALAM KONTRAK YANG MEMUAT KLAUSA ARBITRASE - Bambang Sutiyoso (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2012)
Our research attempts to understand the absolute competence of arbitration and its development in practice as well as the effect of the parties' choice of jurisdiction in a contract containing arbitration clause. This research is expected to be able to explain the competence dispute between arbitration and court to justiciables. We find that choice in jurisdiction would negate the rights of the parties to submit their dispute to district court. In practice, deviation where courts may ignore the arbitration clause, the parties' good faith and consistency of the court play a significant role to further develop the arbitration process. Penelitian yuridis-normatif ini dilakukan untuk mengetahui kompetensi absolut arbitrase dan perkembangannya dalam praktik, serta akibat hukum pilihan forum dalam kontrak berklausula arbitrase bagi para pihak yang berpekara. Penelitian ini diharapkan dapat menerangkan para pencari keadilan perihal sengketa kewenangan mengadili antara arbitrase dan pengadilan. Hasil penelitian menunjukkan bahwa pilihan forum akan meniadakan hak para pihak dan sikap pengadilan yang konsisten memiliki peranan besar untuk mengembangkan arbitrase.